PENGARUH KONFLIK PERAN DAN KEPUTUSAN ETIS MELALUI STRESS KERJA TERHADAP PRESTASI KERJA PEGAWAI WANITA RUMAH SAKIT DAERAH KALISAT KABUPATEN JEMBER - Januar, David (BISMA: Jurnal Bisnis dan Manajemen, 2018)
Abstract: The government builds Regional Hospital of Kalisat Jember to improve local public health service. This research aims to analyze the direct and indirect effects of role conflict, ethical decision, and work stress on work achievement of the women employees working in the Regional Hospital of Kalisat, Jember. This is a quantitative explanatory research with the sample consists of 71 respondents. Data were analyzed by path analysis using SPSS 18. Results show that role conflict has a positive and significant effect on employee work achievement; ethical decision has no effect on employee work achievement. Meanwhile, role conflict has a positive and significant effect on employee performance through work stress; ethical decision has no effect on employee work achievement through work stress; and work stress has a positive and significant effect on employee work achievement. Keywords: Role Conflict, Ethical Decision, Work Stress, and Work Achievement.